Thinopyrum intermedium TiAP1 interacts with a chitin deacetylase from Blumeria graminis f. sp. tritici and increases the resistance to Bgt in wheat. Issue 3 (21st October 2021) - Yang, Yanlin; Fan, Pan; Liu, Jingxia; Xie, Wenjun; Liu, Na; Niu, Zubiao; Li, Quanquan; Song, Jing; Tian, Qiuju; Bao, Yinguang; Wang, Honggang; Feng, Deshun
Summary: The biotrophic fungal pathogen Blumeria graminis f. sp. tritici ( Bgt ) is a crucial factor causing reduction in global wheat production. Wild wheat relatives, for example Thinopyrum intermedium, is one of the wild‐used parents in wheat disease‐resistant breeding. From T . intermedium line, we identified the aspartic protease gene, TiAP1, which is involved in resistance against Bgt . TiAP1 is a secreted protein that accumulates in large amounts at the infection sites of Bgt and extends to the intercellular space. Yeast two‐hybrid, luciferase complementation imaging and bimolecular florescent complimentary analysis showed that TiAP1 interacted with the chitin deacetylase (BgtCDA1) of Bgt . The yeast expression, purification and in vitro test confirmed the chitin deacetylase activity of BgtCDA1. The bombardment and VIGS‐mediated host‐induced gene silencing showed that BgtCDA1 promotes the invasion of Bgt . Transcriptome analysis showed the cell wall xylan metabolism, lignin biosynthesis‐related and defence genes involved in the signal transduction were up‐regulated in the transgenic TiAP1 wheat induced by Bgt . The TiAP1 in wheat may inactivate the deacetylation function of BgtCDA1, cause chitin oligomers expose to wheat chitin receptor, then trigger the wheat immune response to inhibit the growth and penetration of Bgt, and thereby enhance the resistance of wheat to pathogens.